Biochemical methane potential of brewery by-products - Oliveira, João Vítor (2018)
Beer production generates by-products with high energy potential, namely trub (Tr, dead yeast from the fermentation) and spent grain (SG, smashed barley grains). This work investigates the biochemical methane potential (BMP, volume of methane produced per volatile solids of substrateL kg1) of these by-products, performing batch anaerobic biodegradability assays. Single substrates were evaluated as well as a mixture of Tr:SG (1:9, weight), in order to simulate the relative proportion generated in breweries. Tr reached the highest BMP [(515 ± 4) L kg1], still, considering the total amount of by-product available, the mixture of Tr:SG proved to be more rewarding in terms of volume of methane produced. The co-digestion of Tr:SG with crude glycerol (cGly), which was chosen as a co-substrate to promote a synergetic effect on their biodegradability, was assessed by adding different amounts of cGly, up to 33% (in weight). The assay with 10% of cGly achieved the highest methane production [(573 ± 9) L kg1] and biodegradability [(94 ± 2) %], evidencing its potential for energy generation. The co-digestion of these by-products presented a potential electricity production of 206 kWh per cubic meter of beer produced, being capable of serving 80% of the brewers energy needs for heating.